The Effect of Non-linguistic Elements on the Non-Attachment of Adverbs to ‎Governing Factors in the Quran - Abu Suailik, Hamed Ali; Malik, Dalal Abd Alfattah; mohammed, Sara jubair; Noaman, Atheer Tareq (Dirasat: Human and Social Sciences, 2025)
Objectives: There is a non-linguistic component that is linked to the verbal component in every spoken linguistic unit, and it has an impact on determining the meaning of the verbal component. From this perspective, our research aims to identify the non-linguistic elements that govern the construction of the attachment of adverbs to their governing elements. Methodology: This research involves reviewing instances of adverbial attachment in the Quran by analyzing them syntactically and semantically. It also includes a syntactic comparison between the mentioned attachment options to identify the adverbial attachments that, according to grammarians, are deemed semantically impermissible due to non-linguistic element. Results: The study demonstrated the impact of non-linguistic elements on the choices of adverbial attachment in Quran, leading to certain attachments that are rejected by interpretation, whether rationally or doctrinally. Conclusion: It is crucial to connect speech to the context of its use and to consider the requirements of its context, as the meaning of the speech and its purpose dictate the arrangement and sequence of words in a specific order. Words follow the intended meanings, serving as vessels for these meanings. This calls for avoiding the application of a single rule in interpreting a text and instead considering the condition of both the speakers and listeners to achieve the speaker's intended meaning.